SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB DENGAN PHP DAN MYSQL - Kartika Firdausy; Samadri Samadri; Anton Yudhana Yudhana (Universitas Ahmad Dahlan, 2008)
Library are usually used by visitors as media to search a reference and obtain information. Problems at this time is that not many libraries have shaped the web information system for online services. This research aims to analyze and design web-based library information system and testing of the performance of library information systems. Results of research. Results of research shows that the library information system is web-based software built with PHP and MySQL, can work in the Internet network, with the ability to receive data on the WEB library visits, serving registration members get access to a wider, providing services to the availability of information needs click in the form of books, ordering and serving the order book from the members, to serve and return of rental transactions directly.